From humble beginnings to success in the clinic: Chimeric antigen receptor-modified T-cells and implications for immunotherapy. (August 2015) - Firor, Amelia E; Jares, Alexander; Ma, Yupo
In the past 50 years, disease burden has steadily shifted from infectious disease to cancer. Standard chemotherapy has long been the mainstay of cancer medical management, and despite vast efforts towards more targeted and personalized drug therapy, many cancers remain refractory to treatment, with high rates of relapse and poor prognosis. Recent dramatic immunotherapy clinical trials have demonstrated that engineering T-cells with chimeric antigen receptors (CARs) to target CD19 can lead to complete remission in relapsed or refractory B-cell malignancies, generating a great deal of enthusiasm in the field. Here we provide a comprehensive overview of the history of adoptive T-cell therapy, including CARs, in solid tumors as well as hematologic malignancies. CAR therapy has the potential to fundamentally transform cancer treatment with specific and even personalized targeting of tissue- and tumor-specific antigens. However, before CARs become standard first-line treatment modalities, critical issues regarding efficacy, combinatorial regimens, and mechanisms of treatment failure and toxicity will need to be addressed.